Adsorção de fósforo e desenvolvimento do feijoeiro-comum (Phaseolus vulgaris L.) em função da aplicação de silício em latossolo - Stelutti, Ingrid Martins (Universidade Federal de São Carlos, 2022)
One of the main limitations to vegetal growth and development of common bean (Phaseolus vulgaris L.) in acid and highly weathered Brazilian soils is the low availability of phosphorus (P) in solution, due to fixation of this nutrient in soils colloids and insoluble compounds formation with iron (Fe) and aluminum (Al). Among the alternatives to increase phosphate fertilization efficiency highlights the use of competing anions for phosphate adsorptions sites, such as silicate. The silicon (Si) addition in the soil can occur through the stonemeal technology, by the application of silicate rock powders considered as by-products of mining. The objective of this work was to evaluate the effect of Si sources and doses on P adsorption and on development of the common bean plants (cultivar BRS Estilo) on a Rhodic Hapludox soil . The experiment was conducted in a greenhouse, in pots of 11 dm³ (to grow the bean plants) and 1 dm³ (for adsorption analyses), with a completely randomized design in a factorial scheme 5 x 2 + 2, with 11 replications. Experimental treatments included five doses (0, 200, 400, 600, and 800 kg ha-1) and two sources of Si (conventional – Agrosilício Plus® and alternative – silicate rock powder). The P adsorption by the soil samples with different doses and sources of Si was evaluated by batch laboratory experiments, using increasing P doses (0, 40, 80, 160, 320, and 640 mg L-1), and the results were fitted by the Langmuir non-linear model. At 53 days after the plant emergency (peak flowering stage), the application of the two sources of Si did not affect the biometric parameters of stem diameter, plant total height, and shoot dry weight. The rock powder provided the highest shoot fresh weight of the common bean plants. The Agrosilício Plus® in increasing doses favored the increase of the total Falker Chlorophyll Index by plants, differently from the alternative source. The Langmuir non-linear model proved adequate to describe the P adsorption by the Rhodic Hapludox soil. The use of the Agrosilício Plus® and the silicate rock powder did not promote changes in the P adsorption parameters (maximum adsorption and affinity coefficient) by the soil colloids.
Phosphorous adsorption and common bean (Phaseolus vulgaris L.) development as a function of silicon application in an oxisol
Keywords: Adubação fosfatada; Pó de rocha; Rochagem; Isotermas de Langmuir; Feijocultura; Phosphate fertilization; Stonemeal; Langmuir isotherms; Common bean crop; Rock powder; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO